Valuation methods of company’s financial condition (Путеводитель предпринимателя, 2020)
Valuation of company ’s financial condition is very important. The question is the measuring company’s financial condition by different methods. Balance sheet and income statement are used. Methods of company’s valuation are considered too: by discounted cash flow, multiplicators, options. The possibilities and problems of each method are shown.